Gambaran Kejadian Sick Building Syndrome (SBS) pada Pegawai Kantor PT. PLN (Persero) UP3 Surabaya Selatan Kota Surabaya - M. Anas Nasrulloh; Abdul Hakim Zakkiy Fasya (Sehat Rakyat: Jurnal Kesehatan Masyarakat, 2023)
One of the health problem phenomena related to indoor air quality is Sick Building Syndrome (SBS). Sick Building Syndrome (SBS) is a collection of symptoms felt by people who are in the building. The purpose of this study is to provide an overview of the impact of the Sick Building Syndrome (SBS) incident. This research is an analytical observational study. Time of research: February - March 2023. PT. PLN (Persero) UP3 Ngagel, South Surabaya, Surabaya City. from the interview results, there were 45% of respondents who experienced at least 12 symptoms from 20 categories of Sick Building Syndrome (SBS) complaints among office employees of PT. PLN (Persero) UP3 South Surabaya, City of Surabaya. Conclusion: Based on the characteristics of the respondents, it can be seen that the working age of the respondents is mostly> 35 years with the most sex, namely men and the dominant working mass is classified as old > 10 years and smoking habits, namely 73% of respondents do not smoke and 28 respondents have good psychosocial conditions and 2 respondents had poor psychosocial conditions. Of all the symptoms of Sick Building Syndrome, (SBS) complaints that are often felt are dry / hoarse throat (36%), dry skin (29%), skin is often reddish, irritated feeling (21%), rash on the skin, red spots ( 29%), Eye irritation (eyes are often watery/red/itchy, etc.) (36%), Runny nose, sneezing (36%), Chest tightness (36%), Flu-like symptoms (50%), Head dizziness, spinning (29%), Frequent headaches (29%), Drowsiness (36%), Chronic fatigue, lethargy (36%).